Determinan of Factors Associated with Maternity Emergency of Premature Rupture of Membranes: A Literature Review - Ayu Anggraini, Tyas; Lutfiyati, Afi (Universitas Jenderal Achmad Yani Yogyakarta, 2023)
Background: Premature Rupture of Membranes (PROM) is an emergency during to the puerperium which cause serious problems for the mother and fetus. Objective: To identify the determinants factors associated with PROM in pregnant women. Methods: A systematic review of the literature on articles published in the 2017-2022 timeframe. The journal was obtained through 8 databases (Google scholar, PubMed, Garuda Portal, Science Direct, Proquest, Crossref, National Library, Scopus) using